1993
DOI: 10.1063/1.464237
|View full text |Cite
|
Sign up to set email alerts
|

Primary product channels in the photodissociation of methane at 121.6 nm

Abstract: The technique of H(D) atom photofragment translational spectroscopy has been applied to the photodissociation of CH 4 (CD 4 ) at 121.6 nm. Contrary to the previous consensus view, we find simple C-H bond fission to be the dominant primary process following excitation at this wavelength. The resulting CH 3 fragments are formed with very high levels of internal excitation: Some (~25%) possess so much internal energy that they must undergo subsequent unimolecular decay. The present experiments do not provide a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
3
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 37 publications
(2 reference statements)
6
71
3
2
Order By: Relevance
“…It is also a major reactive component in the atmospheres of many other objects in the outer solar system, notably Titan, the largest moon of Saturn. As CH4 only absorbs ultraviolet radiation short of 145 nm [Mordaunt et al, 1993 [Lee and Chiang, 1983], we could perhaps expect an increase of 30%, or more, in the absorption cross sections of CI-I4 when we consider temperatures as low as in Titan's atmosphere (T<200 K). Clearly, it is imperative that methane's absorption coefficients be measured at low temperatures, at least at the Lyman 0• wavelength, but preferably over the whole range of absorption.…”
Section: Absorption Cross Sectionsmentioning
confidence: 99%
“…It is also a major reactive component in the atmospheres of many other objects in the outer solar system, notably Titan, the largest moon of Saturn. As CH4 only absorbs ultraviolet radiation short of 145 nm [Mordaunt et al, 1993 [Lee and Chiang, 1983], we could perhaps expect an increase of 30%, or more, in the absorption cross sections of CI-I4 when we consider temperatures as low as in Titan's atmosphere (T<200 K). Clearly, it is imperative that methane's absorption coefficients be measured at low temperatures, at least at the Lyman 0• wavelength, but preferably over the whole range of absorption.…”
Section: Absorption Cross Sectionsmentioning
confidence: 99%
“…These models differ from the first post-Voyager model [Yung et al, 1984;Yung, 1987] primarily in the updated methane photodissociation scheme [Mordaunt et al, 1993], better characterizations of the eddy diffusion coefficient, and updated reaction rates. Gladstone et al [1996] also presented a photochemical model for the upper atmosphere of Jupiter based on similar reaction sequences.…”
Section: Introductionmentioning
confidence: 99%
“…This value is quite low with respect to direct dissociation. 13 Mordaunt et al 5 also found CH 3 fragments with very high levels of internal excitation. And they suggested that CH 4 molecules prepared in their triplet (S 1 ) A excited state undergo rapid internal conversion to higher vibrational levels of the ground state before dissociation.…”
Section: Discussionmentioning
confidence: 94%
“…Mordaunt et al 5 pointed out the significance of H-atom elimination in this process, and estimated Φ H = 1.0 ± 0.5. The use of H atom Rydberg time-of-flight technique also allowed them to conclude that a very significant part of the H atom fragments is formed concomitant with methyl radicals.…”
Section: Introductionmentioning
confidence: 99%